PENGARUH PENGETAHUAN PAJAK DAN SELF ASSESSMENT SYSTEM TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK HOTEL KATEGORI RUMAH KOS - Tilaar, Brenda V.M; Manossoh, Hendrik; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2017)
Tax of boarding house is included in hotel tax which is one of local tax revenue in Manado City. Government efforts to increase local tax revenues with the self assessment system and tax socialization for the taxpayers to know about taxes and obedient in paying taxes. This study aims to determine how significant the influence of tax knowledge and self assessment system on the level of taxpayer compliance in tax payment category of boarding house either simultaneously or partially. The research method is by using quantitative research. The result of multiple linear regression analysis shows that the tax knowledge and self assessment system have a significant effect on the taxpayer compliance level in tax payment of hotel category of boarding house. Based on the results, the coefficient for adjusted R2 is 0,349. This indicates that the tax knowledge and self assessment system can affect the taxpayer compliance level in the tax payment of the hotel category of boarding house by 34.9%, while 65.1% is determined by other variables not included in this regression analysis.Keywords : tax knowledge, self assessment system, taxpayer compliance, hotel taxes category boarding house